2002
DOI: 10.1248/cpb.50.354
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Study of Allixin, a Phytoalexin Produced by Garlic.

Abstract: Intact constituents or transformation compounds derived from garlic (Allium sativum L.) have been investigated for more than 60 years, and numerous compounds have been isolated and investigated to reveal the relationship between the compounds and biological activities of garlic.1,2) Sulfur-containing compounds, such as allicin, diallylsulfides, dithiins, alliin and S-allylcysteine, have been well investigated by numerous researchers because garlic is rich in sulfur and its sulfur containing compounds were beli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…[9192] Different types of antioxidants are present in different garlic preparations, including water- and lipid-soluble organosulfur compounds like S-allylcysteine and S-allylmercaptocysteine[93] and non-metals like selenium and phytoalexin-like allixin, which are responsible for the protective effect of garlic in several disease models. [9495] Rats fed garlic (0.25 g/kg b. wt.)…”
Section: Spices With Anti-ibd Effectsmentioning
confidence: 99%
“…[9192] Different types of antioxidants are present in different garlic preparations, including water- and lipid-soluble organosulfur compounds like S-allylcysteine and S-allylmercaptocysteine[93] and non-metals like selenium and phytoalexin-like allixin, which are responsible for the protective effect of garlic in several disease models. [9495] Rats fed garlic (0.25 g/kg b. wt.)…”
Section: Spices With Anti-ibd Effectsmentioning
confidence: 99%
“…The phytochemical screening showed that higher proportions of reducing sugars are present in the ethanolic extracts with only the root aqueous indicating appreciable presence while sugars are in low proportion in the shoot aqueous (Table 2). Kodera et al [9] and Dhalel and Markandeya [10] have remarked that the combination of the reducing sugars constitutes a building block in the production of phytoalexins which are antimicrobial substances synthesized by plants. Phytoalexins accumulate rapidly at areas of incompatible pathogen infection.…”
Section: Discussionmentioning
confidence: 99%
“…-During the study on the structure -activity relationship of vanadyl-3-hydroxypyronate [VO(3hp) 2 ]-related complexes (5 -7; Fig. ), we observed that a Figure. Chemical structures of vanadyl complexes complex with allixin, which is found in the extract of dry garlic after storage for two years in dark [22], has extremely high insulin-mimetic and antidiabetic activities [23]. Thus, we identified that bis(allixinato)oxovanadium(IV) [VO(alx) 2 ]; 7; Fig.…”
Section: Activation Of the Insulin-signaling Pathway By Vanadyl Complmentioning
confidence: 91%